Comparative synergistic effects of orthosiphon stamineus benth, teucrium polium l., and berberis vulgaris l. on biochemical markers, glucocorticoid receptors, and histology of hepatocarcinogenic rats - Movahedi, Ariyo (2014)
Nutrition is an important element in the prevention and treatment of cancer. Herbs and fruits have been used for a long time as an alternative remedy in various diseases including cancer. In the present study, decoction of Orthosiphon stamineus,Teucrium polium, and Berberis vulgaris and a combination of all three herbs as synergistic group were studied on hepatocarcinogenic rats to investigate the possible cancer preventive/suppressor effect by these plants. Ninety male Sprague Dawley rats (age: 8±1 weeks, weight: 248.1±7.21g) were purchased from UPM Veterinary Faculty and were housed in individual plastic bottom cages and maintained in a room at 22o C temperature with a 12h light/dark cycle. All rats had free access to the standard rat food pellet and drinking water during the study. Rats were kept for one week as adaptation prior to cancer induction. After that, 10 of 90 rats were sacrificed to obtain the baseline data and the rest were induced with cancer by means of intraperitoneal injection of 200mg/kg diethyl nitrosamine (DEN) dissolved in normal saline. This was then followed by 2 weeks feeding on hepatocarcinogenesis promoter diet made from a mixture of standard rat diet with 2-acetylaminofluorene (0.02% AAF). After this period, the leftover rats (n=60) were weighed again and were randomly separated into five groups of equal animal numbers, i.e., control (NC), O.stamineus (OS), T. polium (TP), B. vulgaris (BV) and the synergistic (SY). Rats were force-feed with the decoction of the herb (0.7ml/100g BW) for 7 months based on their respective herbal treatment group. After the treatment period, the rats were fasted overnight and sacrificed for serum and histology analyses of their livers. All data were analyzed using one way ANOVA followed by Dunkan’s multiple range post hoc test. Differences between groups were considered significantly different when the P value was less than 0.05. Based on the present study BV decoction showed significantly higher level of total phenolic and flavonoids contents as well as antioxidant activity as compared to other groups (p<0.05). The SY decoction group also showed significantly higher level of TPC and TFC as compared to decoction of both OS and TP (p<0.05). Even though, decoction of TP showed significantly lower level of both TPC and TFC, it showed high level of DPPH scavenging activity similar to OS decoction but lower than decoction of BV and SY. Despite the insignificant difference of body weight between the different groups,liver weight of control group was significantly higher as compared to the other groups (p<0.05). Biochemical assay on alkaline phosphatase (ALP), aspartate aminotransferase (AST), and alanine minotransferase (ALT) showed significantly lower level of these markers in BV group as compared to control and other treatment groups (p<0.05). BV groups showed significantly higher total serum lipase and total antioxidant status (TAS) than other groups as well (p<0.05), which showed the possible of beneficial effect of BV on the above mentioned markers. Although SY group also showed significantly higher level of TAS as compared to both control and OS groups (p<0.05), this level of TAS did not show any positive effect on the above mentioned biochemical markers. Both BV and TP groups showed significantly lower values of α2MG, alpha fetoprotein, homocysteine, interleukin 6, lactate dehydrogenase, gamma-glutamyl transpeptidase, and tumor necrosis factor α as compared to other treatment groups( p<0.05). Both BV and TP groups showed significantly higher values of corticosteroid-binding globulin (p<0.05). Light microscopy histological evaluation illustrated that there were significant changes in the lesion score of BV and TP in portal and lobular region compared to OS, SY and control groups. Fluorescence in situ hybridization evaluation of glucocorticoid receptors (GR) showed significantly higher activity of GRs in both BV and TP groups. The present findings showed advantages and disadvantages of the synergistic effects of herbal decoction in cancer prevention or suppression. On the other hand, unlike few previous studies on O. stamineus, even though it showed anticancer properties,the present study could not support strongly the past findings. Overall, the present results showed that the decoction of both B. vulgaris and T. polium has high anticancer activity, which might be due to their either high antioxidant activity or their compounds. Due to these anticancer properties, daily intake of these herbs to prevent cancer in healthy individuals or to suppress and decrease cancer development among patients who are suffering from liver cancer could be recommended.